Population Aging and Inventive Activity - Andreas Irmen; Anastasia Litina (Center for Economic Studies and ifo Institute (CESifo), 2016)
This research empirically establishes and theoretically motivates the hypothesis that population aging has a hump-shaped effect on inventive activity. We estimate this hump-shaped relationship in a panel of 33 OECD countries over the period 1960-2012. The increasing part of the hump captures the awareness that population aging requires inventive activity to guarantee current and future standards of living. The decreasing part reflects the tendency of aging societies to lose dynamism and the willingness to take risks. Policy-wise our analysis suggests that raising the awareness of individuals about the consequences of population aging may facilitate the adoption of strategies and policies encouraging inventive activity and economic growth.
Keywords: J11; O31; O50; O57; 330; population aging; inventive activity; panel estimation